2017
DOI: 10.1155/2017/1875843
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of MicroRNA-375 as Biomarker in Human Cancers Detection: A Meta-Analysis

Abstract: The association between circulating microRNA-375 (miR-375) expression and cancers has been studied; however, the results are inconsistent. We searched PubMed, Embase, and Web of Science for studies concerning the diagnostic value of miR-375 for cancer. The bivariate meta-analysis model was employed to summarize sensitivity, specificity, and diagnostic odds ratio (DOR) for miR-375 in the diagnosis of cancer. Summary receiver operating characteristic (SROC) curve analysis and the area under the curve (AUC) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…A metaanalysis conducted by Yan et al suggested that miR-375 profiling can be used as a screening test for cancers if the specific race and cancer is considered. 27 Additionally, our study results revealed a significant up-regulation in FD-T2DM compared with FD-NGT group. Previous studies conducted on familial aggregation of T2DM showed a higher risk of developing diabetes and pre-diabetes progression in first degree relatives.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…A metaanalysis conducted by Yan et al suggested that miR-375 profiling can be used as a screening test for cancers if the specific race and cancer is considered. 27 Additionally, our study results revealed a significant up-regulation in FD-T2DM compared with FD-NGT group. Previous studies conducted on familial aggregation of T2DM showed a higher risk of developing diabetes and pre-diabetes progression in first degree relatives.…”
Section: Discussionsupporting
confidence: 52%
“…A meta-analysis conducted by Yan et al suggested that miR-375 profiling can be used as a screening test for cancers if the specific race and cancer is considered. 27 …”
Section: Discussionmentioning
confidence: 99%
“…The other common miRNAs such as mir-1269a and b, mir-210-5p, mir-147b, mir-3662-5p, mir-19a-5p and mir-4746-5p suggests that although these miRNAs does not regulate a very large set of genes and pathways, it does have a significant role in the development of cancer as it was seen regulating the most common pathways alongside the highly interactive ones. The up-regulation of the miR-1269a and miR-1269b promotes growth and inhibits apoptosis [41][42][43][44] whereas mir-210-5p over-expression results in an increase of generation of ROS and closely regulates VEGFR gene, Bcl2 which in turn regulates hypoxia and apoptosis in breast and gastric cancer patients [45][46][47][48] . A meta-analysis conducted by Li et al and other similar studies showed the prognostic factor of mir-210 in breast cancer, thereby identifying its therapeutic usage 49,50 .…”
Section: Identification Of Common Mirnas Among Different Cancer Typesmentioning
confidence: 99%
“…Over the past two decades, the regulation of the physiological and pathophysiological processes mediated by miRNAs has been widely studied, including in cancer studies and in studies on inflammatory and infectious diseases [5,[20][21][22][23], as has the identification of miRNAs as a biomarker for infection and for the prognosis of diseases [24][25][26]. Our previous data revealed that the entrance of the parasite into the macrophages initiated the expression of miRNAs.…”
Section: Introductionmentioning
confidence: 99%